E-GOVERNMENT GLOBAL TRENDS AND FUTURE PERSPECTIVE IN INDONESIA - Bambang Tri Atmojo; Nurul Retno Nurwulan (NATAPRAJA, 2020)
E-government has been a global trend in the world. Many countries around the world have implemented E-government since it is believed could give substantial benefits to citizens, businesses, and governments. The aim of e-government is to support the modernization of the public sector, enabling its transparency and effectiveness. With regard to these significant outcomes, e-government could streamline the economic and social development of a nation, including Indonesia. This paper aimed to review the literature on e-government implementation and its future perspective in Indonesia. The inclusion criteria were e-government trends around the world, application of e-government in Indonesia, the factors and the impact of e-government. This study revealed the critical factors that could affect the implementation of e-government in Indonesia. In addition, e-government has a potential to increase transparency, citizen engagement, and gross domestic product (GDP) growth in Indonesia.